Pengaruh Tingkat Persaingan Terhadap Konservatisme Akuntansi Melalui Corporate Governance: Studi Pada Bank Kategori Buku 4 Di Indonesia - Nurmansyah, Agung; Kristianto, Giovanny Bangun; Istiningrum, Farida (Universitas Harapan Bangsa, 2025)
This study aims to examine the effect of competition on accounting conservatism through corporate governance. Accounting conservatism is measured using the market-to-book ratio approach, corporate governance is measured using the Corporate Governance Self-Assessment, and competition is measured using the Lerner Index. The population of this study consists of 35 banking companies listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling, resulting in 6 companies as samples, which are categorized as book 4 banks. The model employed in this study is panel data regression using SPSS version 24. The findings indicate that competition affects accounting conservatism and corporate governance. Furthermore, corporate governance influences accounting conservatism. This study provides evidence that competition affects accounting conservatism through corporate governance.